AI and the News: Challenges Arisen From the Adoption of AI in News Production - George Pleios; Michalis Tastsoglou (Проблеми на постмодерността)
It is premature to assess the impact of AI technologies on the media ecosystem. Nevertheless, a preliminary approach may be proposed, provided that it is founded upon verifiable facts, discernible behaviors, tangible constraints, and practical limitations. In considering the potential contribution of AI to the field of journalism, it is important to adopt a patient and critical approach. The deployment of AI should be assessed following its intended purpose, the nature of the data employed, and the degree of impartiality exhibited by the algorithms and intelligent computing systems. This paper presents a concise overview of the implications of integrating Artificial Intelligence-generated content in news production. The essence of this paper is to present a case for the necessity of human guidance, specifically that of professional journalists, in the deployment of AIGC in news production. In this vein, the article offers an outline of the most significant aspects of the utilization of AIGC in journalistic practice. It focuses on six pivotal concerns, which, thus far, seem to undermine the potential that AI has regarding information management. These issues, representing what in this paper is called as negative side of AI, have to do with: i) data incompleteness, ii) copyright and originality, iii) the opacity of sources, iv) the role of agenda-setting and framing in AIGC, v) the lack of a critical approach, and vi) its relation to fake news.